Differentiated Thyroid Carcinoma of Children and Adolescents: 27-Year Experience in the Yonsei University Health System - Park, Seulkee; Jeong, Jun Soo; Ryu, Haeng Rang; Lee, Cho-Rok; Park, Jae Hyun; Kang, Sang-Wook; Jeong, Jong Ju; Nam, Kee-Hyun; Chung, Woong Youn; Park, Cheong Soo (Journal of Korean medical science, 2013)
Thyroid carcinomas are uncommon in childhood and adolescence. The aim of this study was to analyze clinical features and clinical outcomes of thyroid cancer in the pediatric population treated in the Yonsei University Health System. From September 1982 to June 2009, 90 patients (75 females, 15 males; female:male ratio of 5:1) with differentiated thyroid carcinoma were identified in our institute. The mean age at diagnosis was 15.8 yr old (range 4.8-19.9 yr). Cervical masses were most common clinical manifestations at diagnosis in 65 patients (72.2%). Forty-two patients underwent less than total thyroidectomy and 18 patients underwent total thyroidectomy. Thirty patients (33.3%) had lateral neck lymph node metastasis and seven patients (7.8%) had lung metastasis at the time of surgery. Among the 90 patients, recurrence occurred in 14 patients (15.5%). Mean follow-up period for patients with differentiated thyroid carcinoma was 81.6 months (13-324 months). No patients died of differentiated thyroid carcinoma. Patients with differentiated thyroid carcinoma who were < 20-yr-of-age were present with aggressive local disease and a high frequency of lymph node and distant metastasis. It is recommended that pediatric thyroid cancer should be managed mostly using proper surgical approach with thyroidectomy and lymph node dissection when indicated.